2017
DOI: 10.1111/pce.12893
|View full text |Cite
|
Sign up to set email alerts
|

Does ozone increase ABA levels by non‐enzymatic synthesis causing stomata to close?

Abstract: Reactive oxygen species (ROS) are widely recognized as important regulators of stomatal aperture and plant gas exchange. The pathways through which stomata perceive ROS share many common linkages with the well characterized signalling pathway for the hormone abscisic acid (ABA), a major driver of stomatal closure. Given reports that ABA receptor mutants have no stomatal response to ozone-triggered ROS production, as well as evidence that all steps in the ABA biosynthetic pathway can be non-enzymatically conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 43 publications
(75 reference statements)
0
25
1
Order By: Relevance
“…Furthermore, the most severe loss of function ABA receptor sextuplet mutant, pyr1pyl1pyl2pyl4pyl5pyl8 , lacks a stomatal response to ozone‐induced ROS (Merilo et al ), suggesting that ABA perception may be critical for a ROS‐induced stomatal response. A contrasting model of ROS involvement in stomatal closure has recently been proposed, suggesting that ROS may in fact act by directly catalyzing the sequential oxidation of ABA precursors to ABA (McAdam et al ). This model is based on the results from a series of studies.…”
Section: Angiospermsmentioning
confidence: 99%
“…Furthermore, the most severe loss of function ABA receptor sextuplet mutant, pyr1pyl1pyl2pyl4pyl5pyl8 , lacks a stomatal response to ozone‐induced ROS (Merilo et al ), suggesting that ABA perception may be critical for a ROS‐induced stomatal response. A contrasting model of ROS involvement in stomatal closure has recently been proposed, suggesting that ROS may in fact act by directly catalyzing the sequential oxidation of ABA precursors to ABA (McAdam et al ). This model is based on the results from a series of studies.…”
Section: Angiospermsmentioning
confidence: 99%
“…Avoidance may be explained by stomatal closure during O 3 exposure because the main pathway of O 3 flux into a leaf is through stomata. Ozone is generally known to induce stomatal closure due to the O 3 ‐induced ROS‐mediated modulation of K + channels of the guard cells, a change of Ca 2+ homeostasis, and induction of phytohormones such as abscisic acid (ABA; McAinsh, Evans, Montgomery, & North, ; Kangasjärvi, Jaspers, & Kollist, ; McAdam, Brodribb, & McAdam, ). It has been discussed whether O 3 ‐induced stomatal closure may provide some measures of protection by reducing further entrance of O 3 into the leaves as a stress avoidance response (e.g., Robinson, Heath, & Mansfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that because of strong oxidative stress, pre-exposure to O 3 can prime tomato leaves for an enhanced defense against subsequent herbivorous insect infestation by upregulating the expression of salicylic acid (SA)-dependent defensive gene pathogenesis-related protein and increasing the emission of jasmonic acid (JA)-mediated monoterpene volatiles by tomato plants to decrease the population abundance and feeding fitness of B. tabaci (Cui et al, 2012;Cui et al, 2014). In addition to the SA and JA signaling pathways, O 3 pre-exposure activates the abscisic acid (ABA) signaling pathway, with a significant increase in ABA accumulation via the direct oxidation of the ABA precursor xanthoxin and the expression of ABA-related genes in some species, such as Arabidopsis, tomato, and Chinese pine (Li et al, 2011;McAdam et al, 2017). ABA is an important signal in regulating phloem-sucking insect infestation (Kerchev et al, 2013;Hillwig et al, 2016).…”
Section: Introductionmentioning
confidence: 99%